2022
DOI: 10.1021/acs.macromol.2c01413
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Induced Emission Poly(meth)acrylates for Photopatterning via Wavelength-Dependent Visible-Light-Regulated Controlled Radical Polymerization in Batch and Flow Conditions

Abstract: A robust wavelength-dependent visible-light-regulated reversible-deactivation radical polymerization protocol is first reported for the batch preparation of >20 aggregation-induced emission (AIE)active polyacrylates and polymethacrylates. The resulting polymers possess narrow molar mass distributions (Đ ≈ 1.09−1.25) and high end-group fidelity at high monomer conversions (mostly >95%). This demonstrated control provides facile access to the in situ generation of complex sequence-defined tetrablock copolymers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 59 publications
(109 reference statements)
0
16
0
Order By: Relevance
“…has been proposed as a novel approach to enriching the structural diversity and achieving optimized sensing and signaling properties. [20][21][22][23][24][25][26][27][28] For instance, Ishiwari et al discovered that a four-armed-star-block copolymer based on TPE-appended poly (acrylic acid) with POEGA segments exhibits a better balance of Ca 2+ -sensing and protein-adsorption-resistance properties over copolymers with other topologies. 22 Besides, hyperbranched AIE-active polymers have displayed an improved sensing ability to explosives compared to their linear analogues.…”
Section: Introductionmentioning
confidence: 99%
“…has been proposed as a novel approach to enriching the structural diversity and achieving optimized sensing and signaling properties. [20][21][22][23][24][25][26][27][28] For instance, Ishiwari et al discovered that a four-armed-star-block copolymer based on TPE-appended poly (acrylic acid) with POEGA segments exhibits a better balance of Ca 2+ -sensing and protein-adsorption-resistance properties over copolymers with other topologies. 22 Besides, hyperbranched AIE-active polymers have displayed an improved sensing ability to explosives compared to their linear analogues.…”
Section: Introductionmentioning
confidence: 99%
“…8 Indeed, other research teams have confirmed the strong red-shift of photochemical reactivity, including photo-induced reversible deactivation radical polymerization (RDRP). 9,10 The most notable example is a recent report from the group of Haddleton, showing quantitative conversions of CuBr 2 /Me 6 TREN mediated photopolymerization of methyl acrylates in spectral regions of near zero absorptivity. 10 In addition to unravelling the wavelength resolved reactivity of photochemical reactions, we have applied photochemical reactions to construct complex macromolecules, including single chain nanoparticles (SCNPs), [11][12][13][14] which represent a contemporary research field.…”
mentioning
confidence: 99%
“…9,10 The most notable example is a recent report from the group of Haddleton, showing quantitative conversions of CuBr 2 /Me 6 TREN mediated photopolymerization of methyl acrylates in spectral regions of near zero absorptivity. 10 In addition to unravelling the wavelength resolved reactivity of photochemical reactions, we have applied photochemical reactions to construct complex macromolecules, including single chain nanoparticles (SCNPs), [11][12][13][14] which represent a contemporary research field. [15][16][17] SCNPs have been applied in catalysis [18][19][20][21][22][23] and sensors.…”
mentioning
confidence: 99%
See 2 more Smart Citations